Cyberbullying Victimization : The Risk of Playing Online Games on Adolescents - Christina Andrea; Reny Yuliati (Jurnal Komunikasi Global, 2018)
Online games have become one of the most popular entertainments among adolescents. Instead of being used as a form of entertainment, sometimes online games become a medium of verbal violence or better known as cyberbullying. This study sought to find out whether adolescents who play online games have a greater tendency to become victims of cyberbullying, compared to adolescents who do not play online games. A survey is used by distributing questionnaires to 299 high school students. The results of this study indicate that there is an association between online games exposure and the tendency to become victims of cyberbullying. Adolescents who play online games have a greater tendency to become cyberbullying victims. This finding has implications for prevention and intervention efforts aimed at reducing cyberbullying.